Chance Significances in Case-Control Studies when Using a Long Questionnaire - Scherg, H. (Methods of Information in Medicine, 1980)
The problem of getting per chance significant differences in case—control studies mostly arises when using a long questionnaire or when comparing a large number of characteristics. The number of chance significances increases with the number of statistical tests carried out. Chance significance is demonstrated on a set of empirically collected data divided into two nonsense groups. The variation of chance significances is shown in several random samples from this data set. Chi square analysis of 2 × 2 contingency tables and stepwise discriminant analysis are applied. Suggestions for avoiding chance significances are made. Attention is called to the hazards of stepwise discriminant analysis.
Keywords: Chance Significance; Multiple Inference; Stepwise Discriminant Analysis; Case—Control Study